2017
DOI: 10.3390/plants6040065
|View full text |Cite
|
Sign up to set email alerts
|

TRANSPARENT TESTA GLABRA 1-Dependent Regulation of Flavonoid Biosynthesis

Abstract: The flavonoid composition of various tissues throughout plant development is of biological relevance and particular interest for breeding. Arabidopsis thaliana TRANSPARENT TESTA GLABRA 1 (AtTTG1) is an essential regulator of late structural genes in flavonoid biosynthesis. Here, we provide a review of the regulation of the pathway’s core enzymes through AtTTG1-containing R2R3-MYELOBLASTOSIS-basic HELIX-LOOP-HELIX-WD40 repeat (MBW(AtTTG1)) complexes embedded in an evolutionary context. We present a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 227 publications
2
46
0
2
Order By: Relevance
“…Our finding that the ttg1-23 and ttg1-24 mutations enhance the cpc-1 phenotype (i.e., increase the production of non-hair cells) was unexpected, because previous studies have shown that ttg1 mutants produce more root-hair cells and thus TTG1 is likely involved in non-hair cell specification (Galway et al, 1994). To investigate this discrepancy, we examined additional mutant alleles of the TTG1 gene which have not been analyzed in detail for their root-hair phenotypes (Zhang and Schrader, 2017). We selected three previously described ttg1 mutant lines: ttg1-1, ttg1-9, and ttg1-13.…”
Section: Weak Ttg1 Mutant Alleles Confer a Similar Root Epidermal Phementioning
confidence: 99%
See 2 more Smart Citations
“…Our finding that the ttg1-23 and ttg1-24 mutations enhance the cpc-1 phenotype (i.e., increase the production of non-hair cells) was unexpected, because previous studies have shown that ttg1 mutants produce more root-hair cells and thus TTG1 is likely involved in non-hair cell specification (Galway et al, 1994). To investigate this discrepancy, we examined additional mutant alleles of the TTG1 gene which have not been analyzed in detail for their root-hair phenotypes (Zhang and Schrader, 2017). We selected three previously described ttg1 mutant lines: ttg1-1, ttg1-9, and ttg1-13.…”
Section: Weak Ttg1 Mutant Alleles Confer a Similar Root Epidermal Phementioning
confidence: 99%
“…In addition to root-hair patterning, the TTG1 gene is involved in several other developmental and biochemical pathways in Arabidopsis including trichome patterning, anthocyanin accumulation, seed coat pigmentation, and seed mucilage production (Walker et al, 1999;Miller et al, 2016). For each pathway, TTG1 appears to participate via a MBW complex, although different MYB and bHLH components are used for the five pathways (Zhang and Schrader, 2017). In trichome patterning, GLABROUS1 (GL1) is functionally equivalent to WER and forms a GL1-GL3/EGL3-TTG1 complex to promote trichome differentiation (Larkin et al, 1999;Kirik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hl WRKY1 and Hl WDR1 transcription factors are preferentially expressed in lupulin glands, function as a master regulator to drive the PF and BA biosynthesis pathways [ 18 , 19 ]. The homologs of these two transcription factors have multifunctional roles [ 21 , 22 ]. In this context, it was imperative to understand whether constitutive expression of these two transcription factors could serve as an important strategy to enhance the PF and BA content by analyzing overall impact over the morphological, developmental attributes and other related pathways of hop.…”
Section: Introductionmentioning
confidence: 99%
“…PRR5 recruits TTG1 to subnuclear foci and bHLH92 nuclear enrichment is counteracted by TTG1. In its role as a regulator of early (accessible) developmental traits, TTG1 acts through differential complex composition, in competitive scenarios and is for example trapped by the bHLH factor GL3 in the nucleus of developing trichomes (Balkunde et al 2011;Bouyer et al 2008;Pesch et al 2015;Wester et al 2009;Zhang et al 2019;Zhang & Schrader 2017;Zhao et al 2008). All these scenarios occur at the protein level in dependence of its interactors.…”
Section: Resultsmentioning
confidence: 99%